APLIKASI LAYANAN PELANGGAN BERBASIS WEB DAN MOBILE PADA PERUSAHAAN AIR MINUM: Application, Complaint, Customer Service, Mobile, Water Company - Pariyadi, Pariyadi; Damas Fatih, Muhammad; Anzari, Yandi; Rachmawati, Aulia (LP2M Universitas Nurdin Hamzah, 2025)
The quality of public service is a crucial factor for companies such as the Regional Water Company. The main challenges often faced are the slow handling of customer complaints, difficulty in accessing billing information, and the bureaucratic process of new connection registration. This research aims to design and build an integrated web and mobile-based customer service information system. The research method used is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, and testing. The result of this research is the customer service application, which consists of three platforms: (1) A back office web for administrators, supervisors, and superadmins to manage master data, monitor, and delegate complaints and reports; (2) An Android Mobile Application for Customers, featuring online complaints, complaint tracking, new connection registration, bill checking, self-service meter reading, and news information; (3) An Android Mobile Application for Field Officers, which functions to receive and update the status of complaint work orders. The implementation of this system has successfully transformed manual business processes into digital ones, thereby increasing response speed, data transparency, and customer satisfaction one of them is PERUMDA Air Minum Tirta Mayang.